KEBIJAKAN PEMBERLAKUAN PEMBATASAN SOSIAL BERSKALA BESAR (PSBB) DI MALANG RAYA DALAM PERSPEKTIF POLITIK DAN HUKUM (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2021)
WHO designates the COVID-19 incident as a Public Health Emergency of International Concern (KKMMD/PHEIC). The Indonesian government has also declared it a national disaster. One of the Indonesian Government's strategies in suppressing the spread of Covid-19 is to establish a Large-Scale Social Restriction (PSBB) policy. PSBB Malang Raya was held from May 17 to May 31, 2020. Malang Raya area includes Malang Regency, Malang City, and Batu City. The purpose of writing this paper is to review and discuss large-scale social restrictions (PSBB) in Malang Raya from the legal aspect. The research method used is a normative research method. The implementation of PSBB in Malang City refers to Malang Mayor Regulation No. 17 of 2020 concerning Guidelines for Large-Scale Social Restrictions in the Context of Accelerating The Handling of Corona Virus Disease 2019. During the enactment of PSBB, everyone is required to carry out health protocols. PSBB regulations outlined in various laws and regulations must be obeyed and carried out in a disciplined manner by every resident. On the other hand, the government must also provide minimal basic needs during the PSBB, especially for economically affected residents. Public awareness and compliance with the laws and regulations and the government's appeal to the Large-Scale Social Restriction (PSBB) policy is important not to be violated. After the PSBB period was run for 14 days, the PSBB in Malang Raya was not extended but continued with the preparation of the transition to a new normal life in the midst of the COVID-19 pandemic. However, it is necessary to periodically evaluate epidemiological indicators on the development of COVID-19 cases in Malang Raya. Keywords: PSBB, COVID-19, Malang City